iPSC-neural crest derived cells embedded in 3D printable bio-ink promote cranial bone defect repair - Juliane D. Glaeser; Xianchao Bao; Giselle Kaneda; Pablo Avalos; Phillip Behrens; Khosrowdad Salehi; Xiaoyu Da; Angel Chen; Chloe Castaneda; Pawel Nakielski; Wensen Jiang; Wafa Tawackoli; et al. (Scientific Reports, 2022)
Abstract Cranial bone loss presents a major clinical challenge and new regenerative approaches to address craniofacial reconstruction are in great demand. Induced pluripotent stem cell (iPSC) differentiation is a powerful tool to generate mesenchymal stromal cells (MSCs). Prior research demonstrated the potential of bone marrow-derived MSCs (BM-MSCs) and iPSC-derived mesenchymal progenitor cells via the neural crest (NCC-MPCs) or mesodermal lineages (iMSCs) to be promising cell source for bone regeneration. Overexpression of human recombinant bone morphogenetic protein (BMP)6 efficiently stimulates bone formation. The study aimed to evaluate the potential of iPSC-derived cells via neural crest or mesoderm overexpressing BMP6 and embedded in 3D printable bio-ink to generate viable bone graft alternatives for cranial reconstruction. Cell viability, osteogenic potential of cells, and bio-ink (Ink-Bone or GelXa) combinations were investigated in vitro using bioluminescent imaging. The osteogenic potential of bio-ink-cell constructs were evaluated in osteogenic media or nucleofected with BMP6 using qRT-PCR and in vitro μCT. For in vivo testing, two 2 mm circular defects were created in the frontal and parietal bones of NOD/SCID mice and treated with Ink-Bone, Ink-Bone + BM-MSC-BMP6, Ink-Bone + iMSC-BMP6, Ink-Bone + iNCC-MPC-BMP6, or left untreated. For follow-up, µCT was performed at weeks 0, 4, and 8 weeks. At the time of sacrifice (week 8), histological and immunofluorescent analyses were performed. Both bio-inks supported cell survival and promoted osteogenic differentiation of iNCC-MPCs and BM-MSCs in vitro. At 4 weeks, cell viability of both BM-MSCs and iNCC-MPCs were increased in Ink-Bone compared to GelXA. The combination of Ink-Bone with iNCC-MPC-BMP6 resulted in an increased bone volume in the frontal bone compared to the other groups at 4 weeks post-surgery. At 8 weeks, both iNCC-MPC-BMP6 and iMSC-MSC-BMP6 resulted in an increased bone volume and partial bone bridging between the implant and host bone compared to the other groups. The results of this study show the potential of NCC-MPC-incorporated bio-ink to regenerate frontal cranial defects. Therefore, this bio-ink-cell combination should be further investigated for its therapeutic potential in large animal models with larger cranial defects, allowing for 3D printing of the cell-incorporated material.